2003
DOI: 10.1177/1096348002238883
|View full text |Cite
|
Sign up to set email alerts
|

Measuring The Effect Of Casino-Operated Restaurant Volume On Slot Machine Business Volume: An Exploratory Study

Abstract: Using data from three different North American casino markets, models designed to explain the variance in slot machine business volume (coin-in) produced a significant and positive effect for a variable representing casino-operated restaurant business volume (covers). Simultaneous multiple regression analysis was used to test the audited, secondary data for significance at the .05 alpha level. A 200-day period was examined for each casino property. The results of this study contradicted an earlier, counterintu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 10 publications
(27 reference statements)
6
53
2
Order By: Relevance
“…Autoregressive and movingaverage terms were added on an as-needed basis to remedy specific violations of error-term independence. This method has been successfully employed by researchers seeking to explain the variation in gaming volumes (Lucas, 2004;Lucas et al, 2006;Lucas and Santos, 2003). All hypotheses were tested at the 0.10 alpha level, as the exploratory nature of this research called for a reduction in Type II error.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Autoregressive and movingaverage terms were added on an as-needed basis to remedy specific violations of error-term independence. This method has been successfully employed by researchers seeking to explain the variation in gaming volumes (Lucas, 2004;Lucas et al, 2006;Lucas and Santos, 2003). All hypotheses were tested at the 0.10 alpha level, as the exploratory nature of this research called for a reduction in Type II error.…”
Section: Discussionmentioning
confidence: 97%
“…In an attempt to understand the effectiveness of lottery promotions, Lucas and Bowen (2002) explained 87% of the variation in the daily coin-in levels of a Las Vegas casino. In Lucas and Santos (2003), three separate time series models were used to explain the variation in the daily coin-in produced by a Las Vegas casino and two US riverboats. Their models produced R 2 values of 84, 86, and 94%.…”
Section: Predicting Gaming Volumesmentioning
confidence: 99%
“…Most of the work related to the discovery of influences on slot machine business volume has been performed at the aggregate level (Lucas and Brewer, 2001;Lucas and Bowen, 2002;Lucas and Santos, 2003). These studies all featured a dependent variable measured in terms of daily coin-in, which represented the total amount of wagers accepted in all slot machines.…”
Section: Slot Performance Literaturementioning
confidence: 99%
“…Studies have includedf ocus groups with young people ( Korn, 2005a), self-reported impacts of advertising among problem gamblers (Binde, 2009;Boughton &Brewster, 2002;Grant & Kim, 2001)and measured self-reportedattitudeswithin the general population (Thomas, Lewis, McLeod, &Haycock, 2012). Research has examined the effects of gaming venue promotional incentives,such as freeand discounted play coupons and complimentary hotel accommodation, on aggregate daily gaming volumes (Lucas, 2004;Lucas &Bowen,2002;Lucas, Dunn,&Singh, 2005;Lucas &Santos, 2003;Suh, 2012;Tanford&Lucas, 2011), but with inconsistent findings across studies preventing firm conclusions (Suh, 2012). Binde's( 2007) review noted that studies have generally concluded that, although public concern about the nature and extent of gambling advertising exists,i ts impact on gambling consumption appears small compared to other influential factors.…”
Section: Introductionmentioning
confidence: 99%